An Online Cognitive, Adaptive, Practice based Approach for ITS: An Approach to IT professional certifications - Duweik, Hikmat Jadalla (2008)
With the development of WWW technology, web-based Intelligent Tutoring Systems (ITSs) are becoming an important area of research and development. The key benefit of web-based ITS is that it can be accessed by thousands of learners all over the world. Even though many web-based educational systems have been developed recently, most of them are restricted in functionality, do not provide direction and guidance for individualized learning, and thus fail to take advantage of the distributed nature of the Internet.In this thesis, we present an approach to a practice-based adaptable web-based cognitive intelligent tutoring system that has been applied to build a system that prepares learners for the exam of the International Certificate of ICDL official exam for module 1 (Basic Concepts of Information Technology). ICDL has recently become a de facto standard professional certificate in a wide spectrum of jobs. The system can be used for distance learning/ e-learning or for blended learning approach. It consists of two main modes: the traditional learning mode and the intelligent mode. The traditional learning mode facilitates the learning of concepts by providing full lessons with a fair amount of questions divided between pre lesson quizzes, post lesson quizzes and end of module assessment. The intelligent interactive mode allows the learner to practice concept understanding of the subject matter through means of adaptive self-assessment practices/tests. This is in addition to many other system features including tracking, reporting, assessment/ evaluation tools and some e-communication services and methods.Teachers and students have different interfaces, means of communication, and authorities. The current system consists of nine full lessons with more than 400 questions. An experiment has been conduced to test the system on a random sample of learners to test the effect of the intelligent part over the traditional part on learners learning. The ttest results were impressive and showed that students learning gain on average was 8.1% which is about 3 standard deviations higher when intelligent practiced were involved. The approach is promising and could be extended to cover other subjects and examinations such as SAT, GRE, LSAT, and FE, among others.